A framework for enhancing ethical genomic research with Indigenous communities - Katrina G. Claw (Nature Portfolio, 2018)
Indigenous peoples are still underrepresented in genetic research. Here, the authors propose an ethical framework consisting of six major principles that encourages researchers and Indigenous communities to build strong and equal partnerships to increase trust, engagement and diversity in genomic studies.